2011
DOI: 10.1016/j.phytochem.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and cytotoxicity of oils and eremophilanes derived from various parts of Eremophila mitchellii Benth. (Myoporaceae)

Abstract: A detailed investigation of the wood, leaf, branch and root oil of Eremophila mitchellii (Benth.) was carried out by a combination of GC-FID, GC-MS and NMR. The wood oil was composed predominantly of eremophilanes, a rare class of biologically active, bicyclic sesquiterpenoids. The root oil was also found to contain the eremophilanes together with the zizaene sesquiterpene, sesquithuriferone. 9-Hydroxy-1,7(11),9-eremophilatrien-8-one and the known 1(10),11-eremophiladien-9-one (eremophilone), 9-hydroxy-7(11),9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…In fact, our data extends the results of recent reports which indicated that bicyclic sesquiterpenoids, such as (+)-spathulenol, α-pinene, globulol, viridiflorene and eremophilanes exhibited cytotoxicity against P388D-1 mouse lymphoblast cells in vitro (Beattie et al, 2011). Another recent and relevant publication has shown that the leaf EO of Oreopanax nubigenus and Schefflera rodrigueziana was dominated by the sesquiterpene hydrocarbons germacrene-D (70.1 and 27.6%) and transcaryophyllene (11.8 and 12.2%), respectively.…”
Section: Resultssupporting
confidence: 90%
“…In fact, our data extends the results of recent reports which indicated that bicyclic sesquiterpenoids, such as (+)-spathulenol, α-pinene, globulol, viridiflorene and eremophilanes exhibited cytotoxicity against P388D-1 mouse lymphoblast cells in vitro (Beattie et al, 2011). Another recent and relevant publication has shown that the leaf EO of Oreopanax nubigenus and Schefflera rodrigueziana was dominated by the sesquiterpene hydrocarbons germacrene-D (70.1 and 27.6%) and transcaryophyllene (11.8 and 12.2%), respectively.…”
Section: Resultssupporting
confidence: 90%
“…The majority of known eremophilanes have been isolated from the roots of different plant species, whereas these substances are usually absent in leaves or their content there is very minor (Beattie et al, 2011). Both of the glycosides of eremophilanes known at the present time, fukinoside A (Yoshikawa et al, 2006) and 8-O-(b-D-glucopyranosyl)-2-oxo-eremophila-1(10),8,11-triene (Li and Shi, 2006), have been isolated from the extracts of whole aerial parts of the plants.…”
Section: Resultsmentioning
confidence: 99%
“…The E. mitchellii essential oil industry today owes its viability to the overgrowth of populations in the South Australian Flinders Ranges. Although the timber and essential oils are known for anti-termite activity [110], the essential oil is marketed as an aromatherapy complement to meditation [56].…”
Section: Today's Essential Oil Industrymentioning
confidence: 99%